Monitoring antigenic variations of enterovirus 71: implications for virus surveillance and vaccine development. - Min-Yuan Chia; Wan-Yu Chung; Pai-Shan Chiang; Yeh-Sheng Chien; Mei-Shang Ho; Min-Shi Lee (Public Library of Science (PLoS), 2014)
Enterovirus 71 (EV71) causes life-threatening epidemics in Asia and can be phylogenetically classified into three major genogroups (A ∼ C) including 11 genotypes (A, B1 ∼ B5, and C1 ∼ C5). Recently, EV71 epidemics occurred cyclically in Taiwan with different genotypes. In recent years, human studies using post-infection sera obtained from children have detected antigenic variations among different EV71 strains. Therefore, surveillance of enterovirus 71 should include phylogenetic and antigenic analysis. Due to limitation of sera available from children with EV71 primary infection, suitable animal models should be developed to generate a panel of antisera for monitoring EV71 antigenic variations. Twelve reference strains representing the 11 EV71 genotypes were grown in rhabdomyosarcoma cells. Infectious EV71 particles were purified and collected to immunize rabbits. The rabbit antisera were then employed to measure neutralizing antibody titers against the 12 reference strains and 5 recent strains. Rabbits immunized with genogroup B and C viruses consistently have a lower neutralizing antibody titers against genogroup A (≧ 8-fold difference) and antigenic variations between genogroup B and C viruses can be detected but did not have a clear pattern, which are consistent with previous human studies. Comparison between human and rabbit neutralizing antibody profiles, the results showed that ≧ 8-fold difference in rabbit cross-reactive antibody ratios could be used to screen EV71 isolates for identifying potential antigenic variants. In conclusion, a rabbit model was developed to monitor antigenic variations of EV71, which are critical to select vaccine strains and predict epidemics.